2019
DOI: 10.1002/glia.23748
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of microglial phosphatidylinositol 3‐kinase pathway involved in long‐term potentiation and synaptic plasticity in rats

Abstract: Microglia are the main form of immune defense in the central nervous system. Microglia express phosphatidylinositol 3‐kinase (PI3K), which has been shown to play a significant role in synaptic plasticity in neurons and inflammation via microglia. This study shows that microglial PI3K is regulated epigenetically through histone modifications and posttranslationally through sumoylation and is involved in long‐term potentiation (LTP) by modulating the expression of brain‐derived neurotrophic factor (BDNF), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…Pathway analysis further revealed that several miRNAs including miR-29b-3p, miR-21-5p, miR-19b-3p, miR-101-3p, and miR-30c-5p, were found to be upregulated in activated microglia. These miRNAs target different members of the PI3K/Akt (protein kinase B) pathway, which is involved in the NF-κB-dependent inflammatory response of activated microglia (Saponaro et al, 2012) and long-term potentiation (LTP) through BDNF (Saw et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathway analysis further revealed that several miRNAs including miR-29b-3p, miR-21-5p, miR-19b-3p, miR-101-3p, and miR-30c-5p, were found to be upregulated in activated microglia. These miRNAs target different members of the PI3K/Akt (protein kinase B) pathway, which is involved in the NF-κB-dependent inflammatory response of activated microglia (Saponaro et al, 2012) and long-term potentiation (LTP) through BDNF (Saw et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many signaling pathways are important for microglia-mediated synaptic maintenance in the healthy and pathological brain. Of note, a recent study reported the significant contribution of microglial brain-derived neurotrophic factor (BDNF) towards learning-dependent synapse formation (Parkhurst et al, 2013;Saw et al, 2020). However, the molecular and epigenetic mechanisms underlying microglia-mediated maintenance of neuronal synapses under health and diseases remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…They play key roles in the housekeeping activities of the brain, providing protection and support and maintaining homeostasis in the CNS. While once thought to only play minor supporting roles in the housekeeping of the brain, they have now been shown to be crucial in regulating synaptic plasticity, transmission and memory formation [ 119 , 120 , 121 ]. In the hippocampus, glial cells have long been shown to play integral roles in the regulation of neuronal connections and synaptic transmission [ 119 , 122 , 123 , 124 ], and this finding has not changed over time but has become more and more evident.…”
Section: Epigenetic Regulation Of Hippocampal Glial Cells (Astrocymentioning
confidence: 99%
“…Microglia have been shown to be epigenetically regulated by histone modifications and also post-translationally regulated by sumoylation [ 120 ]. Inhibition HDACs brought about an enrichment H3K9ac in the promoter region of microglial phosphatidylinositol 3-kinase (PI3K) [ 120 ], a key player in neuronal long-term potentiation (LTP) [ 144 ].…”
Section: Epigenetic Regulation Of Hippocampal Glial Cells (Astrocymentioning
confidence: 99%
See 1 more Smart Citation